OPERATING PRINCIPLES OF LASERS AND LEDS - da Fonseca, Adenilson de Souza (Seven Editora, 2026)
This paper discusses the physical fundamentals and applications of lasers (light amplification by stimulated emission of radiation) and LEDs (light-emitting diodes), covering everything from the theoretical basis of quantum mechanics to biosafety criteria. Lasers are discussed as matter-radiation interaction systems that produce beams with high coherence, monochromaticity, and directionality. The stimulated emission mechanisms, postulated by Einstein, and the requirements for light amplification are detailed, including population inversion in multi-energy level systems and the role of optical resonators in maintaining oscillation. The different types of active media and their implications for the properties of the generated beam are reviewed. The operating principles of LEDs are also discussed, based on electroluminescence in P-N semiconductor junctions. The evolution of LEDs is addressed, highlighting energy efficiency and impact on current applications. Finally, the importance of dosimetry and radiological safety is discussed, defining irradiance and fluence parameters and classifying the biological risks associated with the use of these light sources.